Penguatan UMKM Kesenian melalui Digitalisasi Penyewaan Baju Adat Berbasis CodeIgniter di Sanggar Riak Renteng Tingang - Agung Prabowo; Diki Hidayat; Norhayati; Windiarti, Ika Safitri (Abdimas: Papua Journal of Community Service, 2025)
Strengthening traditional art MSMEs through digitalization is a strategic effort to enhance operational efficiency and competitiveness. Sanggar Riak Renteng Tingang, engaged in traditional costume rental in Central Kalimantan, faces various challenges due to manual processes, such as recording errors, difficulties in stock tracking, and inefficiencies in customer data management. Through this community service initiative, a web-based rental information system was developed using the CodeIgniter framework with the waterfall development method and PIECES analysis. The development stages included needs analysis, system design, implementation, testing, and user training. As a result, the system provides features such as stock management, online booking, and integrated customer data recording, improving accuracy, efficiency, and operational transparency. This digitalization simplifies rental management, enhances customer satisfaction, and supports the sustainability of Sanggar Riak Renteng Tingang’s business. The developed system not only addresses operational challenges but also serves as a model for empowering other art MSMEs to adapt to the digital era. With this implementation, Sanggar Riak Renteng Tingang can become more competitive and contribute to the preservation of local culture through technological optimization.